The CD4/CD8 ratio is associated with T lymphocyte functions in long-term virally suppressed patients with HIV - Qing Xiao; Fengting Yu; Liting Yan; Xiaojie Lao; Xuelei Liang; Hongxin Zhao; Liuyue Zhai; Zailin Yang; Xiaomei Zhang; Yao Liu; Fujie Zhang (BMC Infectious Diseases)
Abstract Objective Long-term management of people living with HIV (PLWHs) often relies on CD4+ T cell counts for assessing immune recovery, yet a single metric offers limited information. This study aimed to explore the association between the CD4/CD8 ratio and T lymphocyte activities in PLWHs. Methods 125 PLWHs and 31 HIV-uninfected controls (UCs) were enrolled and categorized into four groups based on their CD4/CD8 ratios: extremely low ratio (ELR) group: 0.4 < CD4/CD8; low ratio (LR) group: 0.4 ≤ CD4/CD8<0.7; medium ratio (MR) group: 0.7 ≤ CD4/CD8<1; high ratio (HR) group: CD4/CD8 ≥ 1. The activation and proliferation phenotypes, mitochondrial functions, and inflammatory indexes of CD4+ T cells and CD8+ T cells were measured, and correlations between the CD4/CD8 ratio and T cell functions were analyzed. Results T cell activation and proliferation were significantly elevated in the ELR group compared to UCs. However, the ELR group had a larger proportion of T cells with lipid peroxidation, mitochondrial lipid reactive oxygen species (ROS), and mitochondrial membrane potential (MMP) abnormalities compared to the other groups. As the CD4/CD8 ratio increased, mitochondrial lipid peroxidation damage decreased and MMP was restored. Additionally, the ELR group had more inflammatory markers in CD4+ T cells. Correlation analysis revealed that the CD4/CD8 ratio was associated with multiple T cell functions, and its correlation coefficient with mitochondrial function was higher than that of CD4+ T cell count. Conclusion The CD4/CD8 ratio is closely related to T lymphocyte functions and is significantly superior to the CD4+ T cell count in reflecting the mitochondrial lipid peroxidation level and mitochondrial functions within T lymphocytes.